2010
DOI: 10.1016/j.bmc.2010.07.044
|View full text |Cite
|
Sign up to set email alerts
|

2,3-Diarylxanthones as strong scavengers of reactive oxygen and nitrogen species: A structure–activity relationship study

Abstract: a b s t r a c tXanthones are a class of oxygen-containing heterocyclic compounds widely distributed in nature. The natural derivatives can present different substitutions in the xanthone core that include hydroxyl, methoxyl, prenyl and glycosyl groups. The inclusion of aryl groups has only been reported for a few synthetic derivatives, the 2,3-diaryl moiety being recently introduced by our group. Xanthones are endowed with a broad spectrum of biological activities, many of them related to their antioxidant abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 42 publications
(32 reference statements)
5
20
1
Order By: Relevance
“…This comes in agreement with previous studies on flavonoids that the strong intramolecular hydrogen bond between the OH group peri to the carbonyl group is generally disadvantageous for the scavenging activity of these compounds [23]. In addition, the new 1-arylxanthones 13a-13c were less potent scavengers than other xanthones possessing a catechol group at position 2 or 3 of their skeleton [24]. It was not possible to determine the scavenging effect of chromones 12a and 12b due to the precipitation that occurred in the tested system.…”
Section: Ros and Rns Scavenging Activity Studiessupporting
confidence: 92%
See 3 more Smart Citations
“…This comes in agreement with previous studies on flavonoids that the strong intramolecular hydrogen bond between the OH group peri to the carbonyl group is generally disadvantageous for the scavenging activity of these compounds [23]. In addition, the new 1-arylxanthones 13a-13c were less potent scavengers than other xanthones possessing a catechol group at position 2 or 3 of their skeleton [24]. It was not possible to determine the scavenging effect of chromones 12a and 12b due to the precipitation that occurred in the tested system.…”
Section: Ros and Rns Scavenging Activity Studiessupporting
confidence: 92%
“…An interesting feature common to all the ROS described is the fact that 6-OH xanthone 13c was shown to have improved scavenging activity when compared to the 8-OH xanthone 13b. Similar to the H 2 O 2 scavenging assays, the ROO scavenging effects of the tested 1-arylxanthones showed to be more efficient than the 2,3-diarylxanthones studied by Santos et al [24]. In fact, they concluded that, unlike to the observed for the other ROS, the introduction of phenolic groups at C-2 or C-3 of the xanthone core is more favourable for the scavenging of ROO that the addition of catechol groups in these positions.…”
Section: Ros and Rns Scavenging Activity Studiessupporting
confidence: 66%
See 2 more Smart Citations
“…Aryl groups linked to xanthones are scarce in natural sources, but several publications reporting their synthesis and/or biomedical potential have been highlighted in literature and reviewed in [13]. In fact, the hydroxylated 2,3-diarylxanthones studied in the present work were already described as capable of scavenging oxygen and nitrogen reactive species [14,15] and inhibiting lipid peroxidation [16]. As so, they can be seen as excellent candidates to act as modulators of the inflammatory process.…”
Section: Introductionmentioning
confidence: 74%